Relationship between antioxidant vitamins, progression of Human Papillomavirus infection and Cervical Intraepithelial Neoplasia: a systematic review (Research, Society and Development, 2020)
This systematic review aimed to elucidate information related to studies that seek to investigate a relationship between antioxidants in patients diagnosed with human papillomavirus and with cervical intraepithelial neoplasia. Searches for articles were submitted to renowned databases. Use the following keywords “HPV, vitamins and antioxidants” to search for materials in English and “HPV and vitamins and antioxidants” to search for materials in Spanish. A total of 378 studies were used and after a screening of articles, based on titles and abstracts, 19 full papers that were approved for eligibility, of which 12 were excluded and thus, only 7 articles printed or selected for selection and were included in the review. The selected studies brought data and results that strengthened the relationship between food consumption and / or plasma samples of antioxidant vitamins with the development of cervical intraepithelial neoplasia. Association between antioxidant vitamins, development of intraepithelial cervical neoplasia and infection by human papillomavirus are relevant. However, it is still necessary that further studies are possible so that the findings can be generalized.